2022
DOI: 10.1093/cid/ciac206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors Associated With Late-Onset Invasive Group B Streptococcal Disease: Systematic Review and Meta-Analyses

Abstract: Background Group B streptococcal (GBS) infection remains one of the most significant causes of late-onset sepsis and meningitis (LOGBS) among young infants. However, transmission routes and risk factors for LOGBS are not yet fully understood. Methods We conducted systematic reviews on clinical risk factors previously reported in the literature (prematurity, low birth weight [<2500 g], antenatal colonization, multiple-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
3
6
0
1
Order By: Relevance
“…In line with previous studies, 3,17,18,22,23 we found that GBS infection was associated with complications of pregnancy and delivery that are also associated with increased risk of NDDs. Thus, when comparing the population of infants having GBS infection with the general population, it may be considered a limitation that parts of the data were aggregated and therefore we were unable to adjust for these variables as possible confounders.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies, 3,17,18,22,23 we found that GBS infection was associated with complications of pregnancy and delivery that are also associated with increased risk of NDDs. Thus, when comparing the population of infants having GBS infection with the general population, it may be considered a limitation that parts of the data were aggregated and therefore we were unable to adjust for these variables as possible confounders.…”
Section: Discussionsupporting
confidence: 93%
“…N. meningitidis , S. pneumoniae , and H. influenzae are mainly transmitted via the respiratory route. Transmission routes of S. agalactiae and E. coli differ by age groups; while this may be foodborne, through contact with farm animals [ 5 ], or from cash money handling [ 6 ], for neonates and infants, transmission mainly occurs vertically (from mother to child) and/or is non-respiratory in the majority of the cases [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…FACTORES DE RIESGO Y MICROORGANISMOS AISLADOS EN LA SEPSIS NEONATAL González J., Sacta D., Buri J., Rodríguez J. ISBN: 978-987-82912-6-0 9 suplementario y trastornos como bajo peso al nacer, inmunodeprimidos, prematuros, malformaciones congénitas, entre otros predisponen a un mayor número de casos nuevos de infecciones que se asocias a los cuidados sanitarios que pueden ser de inicio ya sea precoz o tardío. (3,12) Una revisión sistemática realizada por Shruti M, et al, que incluye 15 estudios asociados a los factores de riesgo de sepsis neonatal en África, señalaron que el peso al nacer y la edad gestacional en el nacimiento son los factores predominantes asociados a esta patología, los resultados estadísticos arrojaron también que los neonatos de sexo masculino, los recién nacidos, la necesidad de ventilación artificial, edad gestacional menor a 37 semanas de gestación y rotura prematura de membranas constituyen factores de riesgo bajo en comparación a los detallados previamente, resultados que presentan gran similitud a los detallados en la presente investigación. (13) Sarmiento Y, et al Detallan en su investigación acerca de la morbimortalidad neonatal asociada a madres toxémicas, en orden de prevalencia se localiza en primer lugar la ruptura prematura de membranas en aproximadamente el 48 % de la madres (77), seguido por sepsis de origen urinario que corresponde al 39,11% (63), sepsis de origen vaginal con 11,8% (18), al comparar estas estadísticas con aquellas expuestas previamente a cerca de los antecedentes prenatales y natales, existe una variación que expresa como principal etiología la sepsis vaginal y en segundo lugar la prematuridad, sin embrago estos resultados no descartan la implicación de ninguno de estos factores en el desarrollo de sepsis neonatal.…”
Section: Discussionunclassified